ABUSING THE ACCUSED? UNPACKING THE USE OF ENTRAPMENT IN UGANDA’S FIGHT AGAINST CORRUPTION - Nanima, Robert Doya (Journal of Anti-Corruption Law, 2023)
In Uganda, an accused person enjoys a right to a fair trial. It is a requirement that the circumstances surrounding the collection and admission of evidence do not violate this right. This article argues that the use of entrapment in cases of corruption may lead to an abuse of the fair trial rights of an accused. The lack of a legislative framework regulating entrapment, the institutional entrenchment of entrapment in the criminal justice system and the inadequate guidance from judgments substantiate this argument. This article recommends amendments to the Criminal Procedure Code Act with a view to preventing abuse of the accused by agents of the criminal justice system.